The Influence of a Single Therapeutic Dose of Methadone on Selected Auditory Functions in Patients Addicted to Opioids and Undergoing Substitution Therapy – a Preliminary Study - TARNOWSKA, Emilia; WICHER, Andrzej; SĘK, Aleksander; GORZELANCZYK, Edward Jacek (Archives of Acoustics, 2018)
The main purpose of this research was to determine the influence of a therapeutic dose of an opioid drug (methadone) on selected auditory functions in patients addicted to opioids (recognition ICD-10; F11) and undergoing substitution therapy. Various hearing tests were used in this research – pure tone audiometry, impedance audiometry, otoacoustic emission measurement, and a speech in noise test – in two sessions, before and after methadone intake. It was found that methadone causes an improvement in speech intelligibility when speech is presented in speech-like noise, and slightly decreases hearing thresholds [dB HL]. Methadone consumption has no significant impact on distortion product otoacoustic emissions levels (DPOAE). In summary, a prescribed methadone dose does not worsen the hearing of opioid-dependent subjects.